Heat preparation and knowledge at the world athletics race walking team championships muscat 2022 - Galan-Lopez, N.; Esh, C. J.; Leal, D. V.; Gandini, S.; Lucas, R.; Garrandes, F.; Bermon, S.; Adami, P. E.; Kajeniene, A.; Hosokawa, Y.; Chrismas, B. C. R.; Stevens, C. J.; et al. (International Journal of Sports Physiology and Performance, 2023)
Purpose: To assess elite racewalkers` preparation strategies, knowledge, and general practices for competition in the heat and their health status during the World Athletics Race Walking Teams Championships (WRW) Muscat 2022.